2015
DOI: 10.1177/1352458515586085
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of lesional and extra-lesional cortical grey matter in relapsing–remitting and secondary progressive multiple sclerosis: A magnetisation transfer and diffusion tensor imaging study

Abstract: Background: In multiple sclerosis(MS), diffusion tensor and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 41 publications
3
21
1
Order By: Relevance
“…As cognitive impairment in MS is known to progress over 5-7 years (Deloire, Ruet, Hamel, Bonnet, & Brochet, 2010), it is possible that CLs influence cognitive function earlier than brain atrophy in patients with MS. (Geurts & Barkhof, 2008;Lucchinetti et al, 2011). Indeed, an MR-based study revealed both focal CLs and generalized GM abnormalities more frequently in SPMS than in RRMS (Yaldizli et al, 2016). Further, changes in extralesional GM were found to be more consistently associated with disability compared with CLs.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…As cognitive impairment in MS is known to progress over 5-7 years (Deloire, Ruet, Hamel, Bonnet, & Brochet, 2010), it is possible that CLs influence cognitive function earlier than brain atrophy in patients with MS. (Geurts & Barkhof, 2008;Lucchinetti et al, 2011). Indeed, an MR-based study revealed both focal CLs and generalized GM abnormalities more frequently in SPMS than in RRMS (Yaldizli et al, 2016). Further, changes in extralesional GM were found to be more consistently associated with disability compared with CLs.…”
Section: Discussionmentioning
confidence: 96%
“…Like progressive MS, inflammatory cortical demyelination, consisting of microglial activation, neurodegeneration, and reduced oligodendrocytes, has also been observed early during the course of MS (Geurts & Barkhof, ; Lucchinetti et al., ). Indeed, an MR‐based study revealed both focal CLs and generalized GM abnormalities more frequently in SPMS than in RRMS (Yaldizli et al., ). Further, changes in extralesional GM were found to be more consistently associated with disability compared with CLs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although these abnormalities occur early in the course of MS (Gallo et al, 2005), more marked DTI abnormalities in the NAWM occur in patients with more significant disability and progressive forms of MS (Preziosa et al, 2011). DTI is also sensitive for the detection of microstructural changes in cortical gray matter (GM), again both in lesions and in normal-appearing tissue, associated with physical disability and cognitive impairment in MS (Yaldizli et al, 2016;Roman and Arnett, 2016). Combined MRI-histopathological studies have demonstrated high correlations between changes in DTI indices and myelin content/axonal count in NAWM and WM lesions, suggesting that DTI abnormalities reflect pathological changes relevant to disability and disease progression in MS (Kim et al, 2006;Schmierer et al, 2007;Budde et al, 2009).…”
Section: Introductionmentioning
confidence: 99%